The assessment on the use of artificial intelligence writing tools as a confidant of business administration student-researchers using technology acceptance model - Jesus, Fhrizz S De; Co, Annalene Grace E (International Journal of Innovative Research and Scientific Studies, 2025)
Artificial Intelligence (AI) has steadily made its way into the academic world; its capabilities have expanded, enabling it to play a more integral role in academic research and writing in various fields like business administration. This research aims to assess the use of Artificial Intelligence writing tools by Business Administration Student-Researchers from Region III in terms of perceived usefulness, ease of use of the Technology Acceptance Model (TAM), perceived attitude towards technology, subjective norms, and facilitating conditions. Additionally, it aims to categorize the students in terms of sex, form of AI writing tools used, and frequency of exposure to AI to determine its relation to their perception of using AI writing tools. This study employed a quantitative descriptive methodology, involving a statistical analysis of frequency and percentage, weighted mean, and Pearson r. In gathering data, the instrument used by the researchers was a questionnaire that underwent expert validation and a series of trial testing. As a result, it was found that most of the Business Administration student-researchers were female, who mostly used grammar and style checkers as a form of writing tool, and tended to use it depending on the situation. It was also found that perceptions of usefulness, ease of use, attitude towards technology, and facilitating conditions are major factors affecting the comfort and acceptance of the students in using Artificial Intelligence in research writing. It was also reported that using AI writing tools presented challenges such as inaccurate responses, difficulty of use, fear of potential dependency, lack of institutional support, and limited access to technology. Finally, it is recommended that institutions take action regarding the growing number of AI tools to better integrate their capabilities for the research writing of students. By conducting seminars, webinars, and training, and tailoring the functions of AI, this could help students use AI more effectively.